Amady Aly Dieng Memoires dun Etudiant Africain Volume II : De lUniversite de Paris a mon retour au Senegal (1960-1967) - Dieng, Amady Aly (Book collections on Project MUSE., 2011)
The advent of formal independence in former French colonies in Black Africa meant the dawn of a new era: the struggle against neocolonialism. African students rallying around this struggle became new strangers and targets for expulsion out of France. The French government of the time resorted, therefore, to massive expulsions against their labour and political organizations. The implementation in 1956 of the Loi-cadre Gaston Defferre? meant to divide up Black Africa under French dominion? and the ensuing explosion of the two great AOF and AEF federations along with the cancellation of scholarship federal commissions will considerably weaken the Fďřation des ťudiants d?Afrique noire en France (FEANF) [African Student Federation in France] in favour of territorial sections. This meant that African governments were to take charge of their own students. In turn, the former used their embassies and scholarship territorial commissions to squelch those student organizations that were hostile to their collaboration with the French authorities. Among the repressive strategies were the cancellation of scholarships and grants to hotels and residences that were reserved for their students (La Maison de la Ct̥e d?Ivoire, du Gabon, de la Haute Volta, du Congo, d?AOF), the creation of pro-government associations such as that of the Senegalese Progressive Union (UPS), the Student Movement for the African and Malagasy Organization (MEOCAM), and the National Union for Students of Ct̥e d?Ivoire (UNECI). This marked the beginning of the decline of the Fďřation des ťudiants d?Afrique noire en France (FEANF). The worm had entered the fruit of unity with the implementation of the Loi-cadre.